Anal Intraepithelial Neoplasia and Squamous Cell Cancer of the Anus - Hoedema, Rebecca E. (Clinics in Colon and Rectal Surgery, 2018)
Anal intraepithelial neoplasia (AIN) is the premalignant condition of the anal squamous tissue. It is associated with the human papilloma virus and is considered the transition prior to the invasive anal squamous cell carcinoma. It is typically asymptomatic and can be either an incidental finding after anorectal surgery or identified when high-risk patient populations are screened. Once AIN is diagnosed, the optimal management remains controversial, partly because the natural history of the disease is unclear. Surgical management of the disease has essentially been replaced by more conservative treatment options and can range from expectant management to topical therapy to photodynamic therapy. The aim of this article is to review the varied treatment options and to briefly review prevention strategies.
Keywords: anal intraepithelial neoplasia; imiquimod; 5-fluorouracil; wide local excision; photodynamic therapy; human papilloma virus